Characteristics of shoreline changes around the South China Sea from 1980 to 2020 - Cui, Yikun; Yan, Fengqin; He, Bin; Ju, Chengyuan; Su, Fenzhen (Frontiers in Marine Science, 2022)
As one of the most sensitive factors in the sea–land interaction zone, the shoreline is significantly influenced by natural processes and anthropogenic activities. Monitoring long-term shoreline changes offers a basis for the integrated management and protection of coastal zones. The spatiotemporal distribution and the utilization types of shorelines had changed a lot, along with the advancement of the socioeconomics of the countries around the South China Sea (SCS) since 1980. However, the changes in shoreline characteristics for a long time around the whole SCS under anthropogenic influence remain uncertain. Using Landsat and high-resolution satellite images, this study monitored the changes in the spatial location and type of shorelines around the SCS from 1980 to 2020. Additionally, the possible reasons for the shoreline changes around the SCS were analyzed. The results showed the following: 1) the length of shorelines around the SCS maintained growth, especially in the 1990s, which increased by 734.8 km, from 28,243.8 km (1990) to 28,978.6 km (2000). 2) The proportion of natural shorelines around the SCS decreased from 92.4% to 73.3% during the past 40 years. Bedrock and mangrove shorelines disappeared most sharply by 34.2% and 21.6%, respectively. The increase of artificial shorelines was mostly driven by the expansion of constructed and aquaculture dikes. 3) The spatial location changes of most artificial shorelines can be attributed to seaward advancement, with an average advancing speed of 7.98 m/year. Of the natural shorelines, 58.4% changed in terms of their location (30.4% advancement and 28.0% retreat). Most natural shorelines around the SCS were threatened by erosion, but the extent of which was largely determined by the shorelines’ own stability, with less influence from the surrounding environment. Artificialization was the most prominent feature of shorelines around the SCS over the past 40 years, which was closely related to the original types of shorelines and the socioeconomic conditions of the area where they are located, and often accompanied by dramatic changes in shoreline morphology and spatial location. In addition, human interventions were not only the dominant factor in shoreline artificialization but also a major driver of natural shoreline protection.